Infection Control During COVID – 19 (Corona Virus) - N. Aravindha Babu, E.P. Sridevi Anjuga2 , E.Rajesh3 , N.Anitha3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The novel coronavirus disease 2019 (COVID-19) has developed into a global pandemic, with its early rootsfrom Wuhan city in China. Many warring nations have placed forward maximum precautionary steps andtools to reduce transmission and decrease fatality rates. Infection control measures are required to preventthe infection and to avoid further spread of the virus and to help control the infection. Restrictive steps suchas social distancing, lockdown, case identification, isolation, contact tracing and quarantine of exposed hadidentified the most effective efforts to monitor the spread of the disease.The risk of cross-infection betweenpatients and dental practitioners may be high due to the characteristics of the dental settings. Strict andreliable guidelines on the prevention of infections are urgently needed for dental practices and hospitals inareas (potentially) affected by COVID-19. This article provides a detailed overview of general and relevantpreventive interventions, methods and prevention of infections in the healthcare and public settings.